Identification and Characterization of Bacillus tequilensis GYUN-300: An Antagonistic Bacterium Against Red Pepper Anthracnose Caused by Colletotrichum acutatum in Korea - Kwon, Hyeok-Tae; Lee, Younmi; Kim, Jungyeon; Balaraju, Kotnala; Kim, Heung Tae; Jeon, Yongho (Frontiers in Microbiology, 2022)
Anthracnose is a fungal disease caused by Colletotrichum species and has detrimental effects on many crops, including red pepper. This study used Bacillus tequilensis GYUN-300 (GYUN-300), which exhibit antagonistic activity against the fungal pathogen, Colletotrichum acutatum. This pathogen causes anthracnose that manifests primarily as a fruit rot in red pepper. There has been little efforts to identify antagonistic bacteria from mushrooms; this strain of bacteria was identified as B. tequilensis using BIOLOG and 16S rDNA sequencing analysis. The genetic mechanism underpinning the biocontrol traits of GYUN-300 was characterized using the complete genome sequence of GYUN-300, which was closely compared to related strains. GYUN-300 inhibited mycelial growth and spore germination of C. acutatum under in vitro conditions. Important antagonistic traits, such as siderophore production, solubilization of insoluble phosphate, and production of lytic enzymes (cellulase, protease, and amylase), were observed in GYUN-300, These trains promoted growth in terms of seed germination and vigorous seedling growth compared to the non-treated control. When red pepper fruits were treated with GYUN-300, the preventive and curative effects were 66.6% and 38.3% effective, respectively, in wounded red pepper fruits; there was no difference between the preventive and curative effects in non-wounded red pepper fruits. Furthermore, GYUN-300 was resistant to several commercial fungicides, indicating that GYUN-300 bacterial cells may also be used synergistically with chemical fungicides to increase biocontrol efficiency. Based on in vitro results, GYUN-300 played a role to control anthracnose disease effectively in field conditions when compared to other treatments and non-treated controls. The results from this study provide a better understanding of the GYUN-300 strain as an effective biocontrol agent against red pepper anthracnose; this form of biocontrol provides an environment-friendly alternative to chemical fungicides.